THE IMPORTANCE OF ABSORPTIVE CAPACITY IN TECHNOLOGY TRANSFER AND ORGANISATIONAL PERFORMANCE: A SYSTEMATIC REVIEW - DA SILVA FLORENCIO, MARCIO NANNINI; DE OLIVEIRA, ANTONIO MARTINS (International journal of innovation management, 2022)
Over the years, the literature on management has advanced in the understanding of the relationship between technology transfer, absorptive capacity and organisational performance. Nevertheless, to date, the number of studies investigating these relationships in a joint manner, showing how the result varies in different contexts, is still rare. This systematic literature review analyses the existing academic literature on the relationship between technology transfer, absorptive capacity and organisational performance by carrying out a bibliometric and qualitative analysis of the literature. The bibliometric analysis provided an overview of the literature, identifying the most prominent and influent journals, countries, institutions, authors and research methods, as well as intersections between the constructs and the temporal evolution of the publications. The qualitative analysis was employed in order to understand, systematise and assess the previous findings on the subjects. The results showed that absorptive capacity is an important factor for effective technology transfer, when taking into account international technology transfer, university-industry collaboration and inter-organisational transfer. The literature converges in indicating that both technology transfer and absorptive capacity have a positive impact on organisational performance, although some existing exceptions need to be considered. Finally, the study provides an agenda for future research based on contextual, methodological and theoretical gaps identified.